Whole Transcriptome Sequencing Reveals How Acupuncture and Moxibustion Increase Pregnancy Rate in Patients Undergoing In Vitro Fertilization-Embryo Transplantation. (28th May 2019) - Cheng, Jie; Jin, Xun; Shen, Jie; Mu, Yanyun; Li, Qian; Xia, Liangjun; Gao, Youling; Xia, Youbing
Abstract : Background . In vitro fertilization and embryo transfer (IVF-ET) technology has been widely used in the therapy of refractory infertility. Previous studies showed that acupuncture can effectively increase the clinical pregnancy rate of IVF-ET. However, the molecular mechanism is unknown. Materials and Methods . In this study, we performed whole transcriptome sequencing for endometrial samples from infertile women who underwent acupuncture and moxibustion therapy or not. Differentially expressed noncoding RNAs (ncRNAs) and mRNAs were identified and their functions were predicted. Besides, a competitive endogenous RNA network was constructed to further interpret the molecular mechanism of acupuncture and moxibustion therapy on infecund patients. In addition, real-time PCR was applied to validate the RNA-seq results. Results . We identified 317 differentially expressed mRNAs and 82 ncRNAs in acupuncture and moxibustion therapy group compared with control group. Functional enrichment analysis suggested that these genes were significantly enriched in GO-BP terms associated with cellular transport, such as ATP hydrolysis coupled proton transport, vacuolar acidification, transferrin transport, and proton transport and metabolic process, including small molecule metabolic process and metabolic process. Pathway enrichment analysis enriched 11 terms, including oxidative phosphorylation, synaptic vesicle cycle, mineral absorption, and metabolic pathways. Four of five selected differentially expressed genes were validated by real-time PCR. Conclusion . Our results suggested that acupuncture and moxibustion therapy might increase the pregnancy rate of patients undergoing IVF-ET by the regulation of ncRNAs.